CALCULATION OF TERNARY Si–Fe–Al PHASE EQUILIBRIUM IN VACUUM DISTILLATION BY MOLECULAR INTERACTION VOLUME MODEL - Liu, Kai; Wu, Jijun; Ma, Wenhui; Yang, Bin; Kong, Lingxin; Zeng, Xianfei; Dai, Yongnian (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
The vacuum distillation of aluminum from Si-Fe-Al ternary alloy with high content of Al is studied by a molecular interaction volume model (MIVM) in this paper. The vapor-liquid phase equilibrium of the Si–Fe–Al system in vacuum distillation has been calculated using only the properties of pure components and the activity coefficients. A signiﬁcant advantage of the model lies in its ability to predict the thermodynamic properties of liquid alloys using only binary inﬁnite dilution activity coefﬁcients. The thermodynamic activities and activity coefficients of components of the related Si-Fe, Si-Al and Fe-Al binary and the Si-Fe-Al ternary alloy systems are calculated based on the MIVM. The computational activity values are presented graphically, and evaluated with the reported experiment data in the literature, which shows that the prediction effect of the proposed model is of stability and reliability.